Machine Learning Techniques Focusing on the Energy Performance of Buildings: A Dimensions and Methods Analysis - Anastasiadou, Maria (2022)
109 “Consumo SMART”. This work is partially funded by national funds through FCT—Foundation for Science and Technology, I.P., under the project FCT UIDB/04466/2020.